2004
DOI: 10.1890/02-5340
|View full text |Cite
|
Sign up to set email alerts
|

CHANGING HABITAT AND HABITAT USE BY BIRDS AFTER THEEXXON VALDEZOIL SPILL, 1989–2001

Abstract: Evaluations of the ecological consequences of environmental accidents can benefit from a long‐term perspective. To assess the effects of the Exxon Valdez oil spill on habitat use and occupancy during midsummer by marine‐oriented birds over a 12‐yr period following the spill in 1989, we conducted surveys in 10 study bays in Prince William Sound, Alaska, USA. These bays varied from completely unoiled to some of the most heavily oiled locations in the spill zone. We used oiling as a quantitative variable with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 45 publications
0
40
0
1
Order By: Relevance
“…These areas differed in habitat features other than oiling, however; moderately and heavily oiled bays had less complex (convoluted) shorelines, more rocky cliffs, less intertidal coverage of Fucus and seagrass, fewer streams supporting salmon runs, and less open conifer woodland in the adjacent supratidal habitats than did unoiled or lightly oiled reference bays (Wiens et al 2001). When these and other habitat variables were included as covariates in the analyses, the significant negative relationships with oiling level disappeared (Wiens et al 2004). Integral Consulting, Inc.…”
Section: Application Of the Ecological Risk Assessment Frameworkmentioning
confidence: 98%
See 3 more Smart Citations
“…These areas differed in habitat features other than oiling, however; moderately and heavily oiled bays had less complex (convoluted) shorelines, more rocky cliffs, less intertidal coverage of Fucus and seagrass, fewer streams supporting salmon runs, and less open conifer woodland in the adjacent supratidal habitats than did unoiled or lightly oiled reference bays (Wiens et al 2001). When these and other habitat variables were included as covariates in the analyses, the significant negative relationships with oiling level disappeared (Wiens et al 2004). Integral Consulting, Inc.…”
Section: Application Of the Ecological Risk Assessment Frameworkmentioning
confidence: 98%
“…Abundances were also lower in western PWS than in eastern PWS well before the spill in 1984, however, suggesting inherent differences in habitat suitability beyond which the spill had only short-term effects. Analyses conducted at a finer scale of resolution (Day et al 1997, Wiens et al 2004 indicated that the population densities of harlequins were substantially lower in oiled than in unoiled bays both before and after the spill, although densities increased proportionately more in the previously oiled bays from 1997 to 2001 than in the unoiled bays. Collectively, these analyses indicate that habitat plays a greater role in determining variations in harlequin abundance in PWS than does oiling history or any lingering effect of the spill.…”
Section: Application Of the Ecological Risk Assessment Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…One assumption using this type of analysis is that although response variables at different sites may differ spatially, those differences track each other over time. This assumption, however, may be violated, reducing confidence in results (Wiens et al, 2004). To bolster confidence and to identify the direction of changes for significant interactions, we visually inspected graphs of data in pre-treatment and treatment periods.…”
Section: Univariate Statistical Techniquesmentioning
confidence: 99%